2007
DOI: 10.1111/j.1460-9568.2007.05854.x
|View full text |Cite
|
Sign up to set email alerts
|

Audition differently activates the visual system in neonatally enucleated mice compared with anophthalmic mutants

Abstract: The occipital cortex, normally visual, can be activated by auditory or somatosensory tasks in the blind. This cross-modal compensation appears after early or late onset of blindness with differences in activation between early and late blind. This could support the hypothesis of a reorganization of sensory pathways in the early blind that does not occur in later onset blindness. Using immunohistochemistry of the c-Fos protein following a white noise stimulus and injections of the anterograde tracer dextran-bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 69 publications
(101 reference statements)
8
46
0
Order By: Relevance
“…Similar anatomical and electrophysiological findings have been reported in early postnatal and adult enucleated mice and rabbits [4143]. Enucleation at birth or congenital microphthalmia in kittens induces auditory activation of the visual cortex, principally area V1 [44, 45], which has also been shown in hamsters, opossums, and mice [4649]. …”
Section: Animal Models Of Cross-modal Plasticitysupporting
confidence: 60%
“…Similar anatomical and electrophysiological findings have been reported in early postnatal and adult enucleated mice and rabbits [4143]. Enucleation at birth or congenital microphthalmia in kittens induces auditory activation of the visual cortex, principally area V1 [44, 45], which has also been shown in hamsters, opossums, and mice [4649]. …”
Section: Animal Models Of Cross-modal Plasticitysupporting
confidence: 60%
“…Further, cortex in the expected location of V1 received aberrant inputs from somatosensory and auditory structures of the cortex and thalamus (Karlen et al, 2006; Figure 8B). Studies in anophthalmic mice have also demonstrated alterations in subcortical connections and large changes in functional organization of “visual cortex” (Godement et al, 1979; Chabot et al, 2007), and studies of congenitally deaf mice show that auditory cortex is taken over by the visual and somatosensory systems (Hunt et al, 2006). Work in experimentally deafened cats supports these data.…”
Section: What Factors Contribute To These Changes?mentioning
confidence: 99%
“…This suggests that auditory inputs from the LGN do not drive V1 activation in blind humans, presumably reflecting the absence of IC–LGN connections. Agreeing closely with this conclusion, Chabot et al (2007) did not observe anatomical connections from the IC to LGN in neonatally enucleated mice. Note, however, that these peculiar connections have been observed in mutant congenitally eyeless mice (Chabot et al, 2007, 2008) and neonatally enucleated hamsters (Izraeli et al, 2002).…”
mentioning
confidence: 61%